Evaluation of the cytotoxicity of products obtained from Calotropis procera (Apocynaceae) (Research, Society and Development, 2020)
Calotropis procera belongs to the Apocynaceae family and is found in the Northeast of Brazil. Several activities are attributed to this species, such as anti-inflammatory, antibacterial and anti-cancer activities. This research aimed to conduct a bioguided study of C. procera in order to isolate and identify triterpenes of the species and evaluate the cytotoxic activity of products of the plant species. The crude ethanolic extract (CEE) was obtained and partitioned. The hexanic phase was chromatographed giving the compound Cp-1, which was identified using spectroscopic techniques and thermal analysis. It was possible to identify Cp-1 as a triterpene called calotropenyl acetate, already reported in the literature. The cytotoxicity test was performed using the MTT technique and it was observed a good activity of CEE and hexanic phase against HL-60 and KS62 lines with an IC50 ranging between 26.8 ± 0.4 µg mL-1 and 47.0 ± 0.5 µg mL-1, besides no toxicity in normal lines, while Cp-1 showed no relevant activity against the tumor cells tested. The results indicated that the species contains in its chemical composition products with pharmacological interest, in addition to cytotoxic for leukemic cells, which can be further explored in complementary studies.